PRE-NUPTIAL AGREEMENT AFTER THE ENACTMENT OF DECREE BY CONSTITUTIONAL COURT OF INDONESIA NUMBER: 69 / PUU-XIII / 2015 TO THE THIRD PARTY - Liliana Tedjosaputro (Faculty of Law Universitas 17 Agustus 1945 Semarang, 2017)
Pre-nuptial agreement which was originally provided in Article 119 of the Civil Code and Article 29 of Act Number 1 of 1974 may only be made upon or before the marriage is conducted. As for foreigners who conduct mixed marriage with Indonesian Citizen, without having pre-nuptial agreement before marriage is conducted or upon the marriage is conducted, the joint property in marriage shall be deemed as foreign property and in accordance with the Basic Agrarian Law, land and building which is registered under the name of Indonesian citizen who conduct mixed marriage with foreigners, which is not transferred after one year will become state property. Afterwards the Constitutional Court issued Decree Number : 69/PUUXIII/2015 which grants permission that pre-nuptial agreement may be made after the marriage is conducted. Can after marriage pre-nuptial agreement be applied retroactively without harming the third party? Pre-nuptial agreement may be made after the marriage is conducted if it's implementation does not harm the third party. Because after the pre-nuptial agreement is made the conjugal property is no longer joint property. The husband and wife property's title shall become their own property title respectively. Thus, Indonesian citizen property shall remain Indonesian citizen property, foreign citizen property shall remain foreign citizen property in mixed marriage. Land which is owned by Indonesian citizen may still be owned by Indonesian citizens because there is no joint ownership of property by foreigncitizen.